The microbiome of the ice-capped Cayambe Volcanic Complex in Ecuador - Díaz, Magdalena; Monfort-Lanzas, Pablo; Quiroz-Moreno, Cristian; Rivadeneira, Erika; Castillejo, Pablo; Arnau, Vicente; Díaz, Wladimiro; Agathos, Spiros N.; Sangari, Félix J.; Jarrín-V, Pablo; Molina, C. Alfonso (Frontiers in Microbiology, 2023)
A major challenge in Microbial Ecology is to understand the principles and processes by which microbes associate and interact in community assemblages. Microbial communities in mountain glaciers are unique as first colonizers and nutrient enrichment drivers for downstream ecosystems. However, mountain glaciers have been distinctively sensitive to climate perturbations and have suffered a severe retreat over the past 40 years, compelling us to understand glacier ecosystems before their disappearance. This is the first study in an Andean glacier in Ecuador offering insights into the relationship of physicochemical variables and altitude on the diversity and structure of bacterial communities. Our study covered extreme Andean altitudes at the Cayambe Volcanic Complex, from 4783 to 5583 masl. Glacier soil and ice samples were used as the source for 16S rRNA gene amplicon libraries. We found 1) effects of altitude on diversity and community structure, 2) the presence of few significantly correlated nutrients to community structure, 3) sharp differences between glacier soil and glacier ice in diversity and community structure, where, as quantified by the Shannon γ-diversity distribution, the metacommunity in glacier soil showed more diversity than in glacier ice; this pattern was related to the higher variability of the physicochemical distribution of variables in the former substrate, and 4) significantly abundant genera associated with either high or low altitudes, that could serve as biomarkers for studies on climate change. Our results provide the first assessment of these unexplored communities, before their potential disappearance due to glacier retreat and climate change.